The Effect of Evogliptin Tartrate on Controlling Inflammatory Pain - Pyung Goo Cho; Jun Ho Jang; Sukjin Ko; Dong Ah Shin; Seungsoo Chung; Min Cheol Chang (Biomedicines, 2023)
Background: Evogliptin tartrate inhibits dipeptidyl peptidase-4 (DPP-4), boosting glucagon-like peptide 1 (GLP-1) secretion and improving insulin release and glucose tolerance, while also exerting anti-inflammatory effects. We investigated its anti-inflammatory and analgesic effects. Methods: Forty male Sprague Dawley rats were divided into (N = 10 in each): (1) naïve, (2) complete Freund’s adjuvant (CFA) inflammation + evogliptin tartrate (once for 10 mg/kg) (CFAE), (3) CFA + vehicle (same volume with normal saline with evogliptin tartrate/once) (CFAV), and (4) CFA + indomethacin (5 mg/mL/kg/1 time) (CFAI) groups. CFA was injected subcutaneously into rat plantar regions, and medications (evogliptin tartrate, vehicle, and indomethacin) were administered orally for 5 days. Post treatment, blood from the heart and plantar inflammatory tissue were collected to assess inflammatory cytokines. Evogliptin tartrate effects on controlling inflammation and pain were evaluated by measuring rat plantar paw thickness, paw withdrawal threshold, dorsal root ganglion (DRG) resting membrane potential, DRG action potential firing, and cytokine (TNF-α and IL-1β) levels. Results: Compared with the naïve group, plantar paw thickness, cytokine (TNF-α and IL-1β) levels, DRG resting membrane potential, and DRG action potential firing increased, whereas the paw withdrawal threshold decreased in all CFA groups. However, CFAE and CFAI rats showed recovery. The degree of CFAE recovery resembled that observed in the CFAI group. Conclusions: Evogliptin tartrate mirrored the anti-inflammatory pain relief of indomethacin. We aim to broaden its use as an anti-inflammatory drug or pain relief drug.